The contribution of intrinsic motivation, extrinsic motivation, and motor ability to students’ physical education learning outcomes - Gusrianto Gusrianto; Yanuar Kiram; Anton Komaini; Padli Padli (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study aimed to examine the contribution of intrinsic motivation, extrinsic motivation, and motor ability toward practical learning outcomes in Physical Education, Sports, and Health among upper-grade elementary school students. This study employed a quantitative associative design involving 53 students selected through purposive sampling. Data were collected using motivation questionnaires, standardized motor ability tests, and documentation of practical learning outcomes. Data analysis included descriptive statistics, prerequisite tests, and simple as well as multiple regression analyses using Jamovi 2.6.44. The findings indicated that intrinsic motivation contributed significantly to learning outcomes (R² = 0.383; p < 0.001), while extrinsic motivation contributed 0.375 (p < 0.001). Motor ability showed the strongest contribution with an R² value of 0.420 (p < 0.001). Simultaneously, the three variables explained 56.8% of the variance in practical learning outcomes (R² = 0.568). The findings emphasize that practical learning achievement is influenced by both motivational and physical factors. Motor ability emerged as the strongest predictor, while motivation strengthened student participation and engagement during learning activities.